A global history of architecture - Ching, Francis D. K. 1943-; Jarzombek, Mark; Prakash, Vikramaditya (Hoboken, New Jersey : John Wiley & Sons, 2017)
"A Global History of Architecture, Third Edition has been updated and revised throughout to reflect current scholarship, including an expanded section on contemporary global architecture. Spanning from 3,500 b.c.e. to the present, this unique guide is written by an all-star team of architectural experts in their fields who emphasize the connections, contrasts, and influences of architectural movements throughout history"--
Includes bibliographical references (pages 811-820) and index.
ARC
Karim International, Trim Education
Keywords: Architecture -- History; ARCHITECTURE / History / General; Architecture